Avaliação comparativa do uso da furosemida em bolus ou infusão contínua no tratamento de cães com doença degenerativa valvar - Gomez Ortiz, Edna Mireya [UNESP] (2015)
Congestive heart failure (CHF) is a syndrome that leads to inadequate blood supply to the tissue due to heart dysfunction and is treated with furosemide in intermittent bolus (BI). However, studies in humans with CHF showed that furosemide continuous rate infusion (CRI) showed better efficacy and safety for the administration in BI. Therefore, the aim of this study was to compare the effectiveness of the diuretic furosemide in CRI and BI in dogs with mitral valve myxomatous degeneration. To this end, the study included 20 dogs between 8 and 12 years old, weighing between 8 and 15 kg, and ICC classes Ia, Ib and II - ISACHC, and the control group. CRI for the treatment, the dogs received 0.66mg/kg IV furosemide as a loading dose followed by 0.66mg/kg/h for 8 hours. BI treatment the dogs received 3 mg / kg IV furosemide at 0 and 4 hours. The dogs were treated by CRI and 15 days later, the same dogs were treated by BI. For both treatments, the same volume of fluid and urine production was quantitated was administered hourly. The water intake, urine specific gravity, urine pH were evaluated per hour. The variable blood, hematocrit (Hct), hemoglobin (Hb), creatinine (creat), urea, total protein (TP), albumin (ALB) and electrolytes sodium (Na), potassium (K), magnesium (Mg), calcium (Ca) and phosphorus (P) were evaluated every two hours. The weight and Doppler echocardiographic variables were evaluated before and after treatment. The urinary output per hour (mL/kg/h) and total (mL/kg/8h) was higher in the treatment CRI in the control group and CHF class II (p <0.05). The water intake, urine specific gravity, urinary pH difference, weight loss, Ht, Hb, urea, creat and phosphorus parameters along with the differences in Doppler echocardiographic variables were not significantly different between treatments (p> 0.05). The furosemide continuous infusion rate has increased urine output in dogs with MMVD functional classes Ia, Ib, II and ...